Members of the Raton Lions Club (Raton, NM Raton Range, 1996)
This article is about the Raton Lions club, Spouses and guests enjoying a festive dinner at the Sweet Shop following the lighting of the City of Bethlehem.
Newspaper article 5oth Annual
Master list item #: 17
File location is in the Raton file Cabinet
Keywords: Abeyta, Jose R; Brown, Betty; French, Pat; Main, Debbie; Main, Sandra; Mullings, Jim; Brown, Wesley W. "Possum"; Roper, Jim; Apache, Joe -- Mayor; Cheasebro, Wall; Roper, Flo; Young, Jim; Raton Lions Club; Fistive Dinner; Speeches; Holiday Traditions; Christmas Parties; City of Bethlehem; Raton, New Mexico